The Development of Mental Health Difficulties in Young People With and Without Developmental Language Disorder: A Gene–Environment Interplay Study Using Polygenic Scores. - Toseeb, Umar; Vincent, John; Oginni, Olakunle A.; Asbury, Kathryn; Newbury, Dianne F. (Journal of Speech, Language & Hearing Research, 2023)
Purpose: Young people with developmental language disorder (DLD) have poorer mental health than those without DLD. However, not all young people with DLD are equally affected; some have more mental health difficulties than others. What explains these differences remains unclear. Method: Data from a community cohort study, the Avon Longitudinal Study of Parents and Children, were analyzed to investigate genetic and environmental influences on the development of mental health difficulties at five time points from childhood (7 years) to adolescence (16 years) in 6,387 young people (8.7% with DLD). Regression and latent class models were fitted to the data. Results: Polygenic scores (PGSs), indices of genetic risk, for common psychiatric disorders (major depressive disorder, anxiety disorder, and attention deficit hyperactivity disorder) predicted mental health difficulties in both groups (with and without DLD). The presence of DLD, in some instances, amplified mental health difficulties for those with high genetic risk for common psychiatric disorders. Subgroups of children with similar developmental trajectories of mental health difficulties were identified. Young people with DLD were more likely than those without DLD to follow mental health subgroups characterized by consistently high levels of difficulties during development. PGSs, socioeconomic status, and the early home environment distinguished subgroups with low mental health difficulties from those characterized by high levels of difficulties, but these effects did not differ based on DLD status. Conclusions: These findings suggest that, for the most part, both genetic and environmental risk affect the development of mental health difficulties in a cumulative way for young people with DLD (and those without). Some analysis did, however, suggest that genetic risk for common psychiatric disorders might manifest more strongly in those with DLD compared with those without DLD.